The incidence of suspected white spot syndrome virus in semi-intensive and extensive shrimp farms in Bangladesh: Implications for management - Karim, M.; Sarwer, R.H.; Brooks, A.C.; Gregory, R.; Jahan, M.E.; Belton, Ben (Hindawi Limited, 2012)
The study was conducted to assess key factors influencing suspected white spot syndrome virus (WSSV) disease and associated shrimp production and economic performance in three contrasting black tiger shrimp (Penaeus monodon) culture technologies promoted by the United States Agency for International Development funded Shrimp Quality Support Project (SQSP) in Bangladesh. A total of 350 traditional, 315 Modified Traditional Technology1 (MTT1), 36 MTT2 and 88 Closed System Technology (CST) farmers from 10 sub-districts in three districts of Khulna division were surveyed following random sampling at the end of the project. Binomial probit regression analysis revealed that smaller newly constructed ponds (known locally as gher) were less susceptible to WSSV, provided aquatic weeds were controlled using chemicals. Removal of sludge from ghers also had a positive effect, irrespective of technology and location. It was also shown that stocking of screened shrimp postlarvae (PL) does not guarantee protection against WSSV (t = 1.39, P > 0.05). Higher shrimp production was obtained by farmers practicing CST, followed by those operating MTTs and traditional technology respectively. Farmers who adopted CST also gained higher profitability followed by those operating MTT1, MTT2 and traditional technology.